Doppler Evaluation of the Thyroid in Pediatric Goiter - Mahmutyazicio?lu, Kamran; Turgut, Mehmet (My University, 2004)
Purpose. The aim of this study was to identify any changes in Doppler parameters in the thyroid arteries of pediatric patients with a clinical diagnosis of goiter living in an area where goiter is endemic. Patients and Methods. In this prospective study, 20 pediatric patients with simple endemic goiter and 20 age-matched healthy subjects underwent sonographic examination. The resistance index (RI) and peak systolic velocity (PSV) on duplex sonography were measured from the inferior thyroid arteries, and the thyroid gland volume was recorded. Serum thyrotropin, free T3 hormone, and free T4 hormone levels were measured in both groups. Results. The mean thyroid volume (± standard deviation) was significantly higher in the patients than in the healthy subjects (7.2 ± 1.4 ml versus 3.2 ± 1.1 ml; p < 0.01). The mean RI values for the thyroid arteries were significantly lower in the patient than in the control group (0.58 versus 0.70, respectively; p < 0.05). The mean PSV of the thyroid arteries was significantly higher for the patients than for the healthy subjects (mean, 36.7 cm/second versus 18.3 cm/second, respectively; p < 0.05). There was no correlation between the Doppler parameters and any of the hormone levels evaluated. Conclusions. In the arteries supplying the thyroid gland in a pediatric population, Rls were lower and PSVs higher in the patients with diffuse goiter than in the healthy control group. We discuss iodine deficiency as a possible mechanism for these changes. © 2003 Wiley Periodicals, Inc.
Keywords: Doppler ultrasonography; Goiter; Iodine deficiency; Pediatrics; Thyroid